CULTURAL CONTINUITY OF UTTARAKHAND’S RAMLILA - Gupta, Punita; Badhani, Chandra Shekhar; Nishant, Nipun (International Journal of Research -GRANTHAALAYAH, 2025)
Ram is the center point of the value concept of Indian wisdom" (Ramchand 2024: 169). Ramlila is an integral part of Indian culture and traditions, through which the life and ideals of Ram are presented in a dramatic form. This performance is very important from religious, social and cultural point of view. The tradition of Ramlila holds a special place in Uttarakhand, where it is a symbol of cultural heritage and community participation. The traditional form of Ramlila in Uttarakhand is full of localness, which is celebrated as a cultural festival in open spaces of villages, towns and cities, government land or buildings and the land of the staging committee. About 44 male and 18 female characters play an important role in the staging of Ramlila. The characters for the performance are usually selected from the local community, who display the traditional art of performance. The roles of the characters, traditional costumes, and the use of local musical instruments make this event even more special and picturesque. These performances show the inclusion of religiosity and customs, which gives the audience a unique experience of spirituality and entertainment. Technology and modernity have also influenced the form of Ramlila performance, such as the inclusion of modern sound and light arrangements, digital technology, modern songs and music and contemporary contexts make Ramlila more attractive. These technological changes have played an important role in connecting the young audience. The dramatic inclusion of contemporary problems and issues also makes the performance relevant and entertaining. Ramlila organizing committees consider Ramlila not only a religious event, but also a means of promoting social unity and community spirit. Along with spreading moral and religious values, this event is also helpful in preserving regional traditions. In Uttarakhand, this event is working to keep people connected to their cultural roots from generation to generation. Uttarakhand’s Ramlila is known for its historicity, staging style, cultural diversity, and community participation. It is a wonderful example of harmony between tradition and modernity, where a confluence of traditional culture and modern presentation is seen. The study of Uttarakhand’s Ramlila provides an opportunity to understand its historicity, staging style, cultural neutrality, community participation (especially in the context of women’s participation), and the balance between tradition and modernity. It is not only a religious and cultural heritage, but also a living tradition, which accepts the change of time and maintains its relevance and originality as well as carries out the process of change and continuity. This is a part of the research work done under the ICSSR funded program "Comparative study of the history of Ramlila staging and contemporary styles of presentation in Uttarakhand and social impact assessment of women’s participation".